2011
DOI: 10.1108/09654281111144265
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of medical students' perceptions of three experiential methods

Abstract: Purpose -This study aims to compare Finnish medical students' perceptions of the suitability of three experiential methods in learning interpersonal communication competence (ICC). The three methods it seeks to explore are: theatre in education; simulated patient interview with amateur actors; and role-play with peers. The methods were introduced in a pilot course of speech communication. Design/methodology/approach -Students (n ¼ 132) were randomly assigned to three groups. The data were collected via questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
(42 reference statements)
1
13
0
2
Order By: Relevance
“…However, our earlier study showed that there were some differences in respondents' perceptions of the method's helpful and unhelpful elements (Koponen et al 2011). Respondents who had experienced communication skills training with the TIE method found being active (the method stimulated them to think and led to new thoughts) and reflective discussions together with peers in the modified forum theatre stage (respondents appreciated being able to intervene in the play by stopping the action and discussing with the group when several viewpoints and proposals came up) as helpful elements.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, our earlier study showed that there were some differences in respondents' perceptions of the method's helpful and unhelpful elements (Koponen et al 2011). Respondents who had experienced communication skills training with the TIE method found being active (the method stimulated them to think and led to new thoughts) and reflective discussions together with peers in the modified forum theatre stage (respondents appreciated being able to intervene in the play by stopping the action and discussing with the group when several viewpoints and proposals came up) as helpful elements.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot claim that one method was more effective than others. It would nevertheless be interesting to explore the results of our earlier study, which compared medical students' perceptions of the suitability of TIE, SPs and RP in learning interpersonal communication competence (Koponen et al 2011). The respondents were the same medical students as in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations